Determination of Phosphate as an Ion-Association Complex of 11-Molybdovanadophosphate and Diindodicarbocyanine Based on Selective Oxidation of Excess Dye - Andriy B. Vishnikin; Svitlana V. Khlyntseva; Yaroslav Bazel; Ioseph Balogh; Ihor E. Barchiy (Molecules)
The elimination of absorbance of excess dye by selective oxidation was first proposed for analytical methods using the formation of ion-association complexes (IAs). On this basis, a new sensitive and selective spectrophotometric method for the determination of phosphate in the form of the IA of 11-molybdovanadophosphate with diindodicarbocyanine (DIDC) was developed. Symmetric diindodicarbocyanine and diindotricarbocyanine dyes can be completely oxidized by sufficiently strong oxidizing agents such as permanganate, dichromate, cerium (IV), and vanadate. Of the three dyes investigated (DIDC, N,N’-dipropyldiindodicarbocyanine, and diindotricarbocyanine), the best results were obtained with DIDC. A mixture of molybdate, vanadate, and nitric acid was preferably used as an oxidizing agent. Selective decolorization of only free dye ions, as well as changes in the IA spectrum compared to the dye spectrum, were explained by the isolation of the dye due to the formation of poorly soluble IA nanoparticles and changes in the redox potential of the dye due to its aggregation. The following optimal conditions for phosphate determination were found: 0.3 M nitric acid, 0.43 mM sodium molybdate, 0.041 mM sodium vanadate, 0.015 mM DIDC, and 18 min for the reaction time. The molar absorptivity of the IA was 1.86 × 105 mol−1·L·cm−1 at 600 nm, and the detection limit for phosphate was 0.013 µM. The developed method was applied to the determination of phosphate in natural water samples.